SINTESIS DAN KARAKTERISASI SIFAT MEKANIK BIOKOMPOSIT FILLER SHORT FIBER KULIT ROTAN HASIL FERMENTASI - Atin A. Anggraeni (Jurnal Biofisika, 2012)
Rattan bark fiber as synthetic fiber at composite filler replacement has been used in this research. The extraction of the rattan bark fiber are done using a fermenta tion method of Aspergillus niger and milling.The fiber that created are long and short fiber (2  mm)  in  shape.  Biocomposite  synthesis  using  blending-hot  press  method  that suitable  with  variant  mechanical  standardization  test,  ASTM  D2240  for  hard  tools test,  ASTM D1822 for pull tools test. Rattan bark fiber act as filler, polypropylene as matrix,  and  maleat  acid  as  coupling  agent.  Mechanical  measurement  test  of biocomposite  sf  (5%)  and  sm  (5%)  result  shows  that  the  hardest  point  are  4.33  ±0.17 Mpa. The sf (5%) and sm (5%) biocomposite pulling power are  140.12 ± 0.76 Mpa.  Biocomposites  filler  short  fiber  rattan  skin  fermentation  method  has  the potential to be further developed as a multi-functional materials.